32.3.9.2 1-Phosphorus-Functionalized 2-(Organooxy)alkenes (Update 2021) - Grimmer,J.; Krieg,S.-C.; Manolikakes,G. (Knowledge Updates 2021/1, 2021)
This is an update to the earlier Science of Synthesis contribution (Section 32.3.9) covering the synthesis of 1-phosphorus-functionalized 2-(organooxy)alkenes. It focuses on the literature published in the period 2006 to 2019.
Keywords: Referencework; Science of Synthesis; alkenes; organophosphorus compounds; phosphorylation; methylation; cyclization; cycloaddition; methanolysis; acylation